The perverse logic of external evaluations: their implication in educational medicine - Garcia, Amanda Trindade [UNESP]; Marques, Jaqueline Belga [UNESP]; Mosca Giroto, Claudia Regina [UNESP] (Univ Federal Sergipe, 2021)
A perverse logic permeates the education of the first years of elementary school that materializes the child and becomes a product in the educational process. The education scenario in Brazil develops writing learning as a challenge, and external audits are tasked with revealing this problem, initiating a mercantilist logic in education, or studying for medical education. The methodological option of the present study was subsidized by the Bakhtinian assumptions and by the thoughts of the historical-cultural theory or that led to an analysis of the educational processes with the evidence of the need to return to the interior of the school, also reviewing, precarious training and practice.
Keywords: Diseases of not learning; External assessments; Medicalization of Education; Written language